Comparison of the impact of childhood psoriasis on mothers' and fathers' quality of life – does gender of a caregiver play a role?. (9th October 2020) - Żychowska, M.; Reich, A.; Maj, J.; Jankowska‐Konsur, A.; Szepietowski, J. C.
Abstract: Background: Psoriasis is a chronic skin condition that in one third of cases starts in the first two decades of life. The disease might impact the quality of life (QoL) of the affected children and their caregivers. The issue of gender differences in the assessment of psychological burden of dermatological conditions has been the subject of few studies with contradictory results. Objectives: The aim of this study was to investigate the differences in the impact of childhood psoriasis on mothers' and fathers' well‐being using Family Dermatology Life Quality Index (FDLQI). Methods: Forty‐five children with psoriasis (31 girls and 14 boys; mean age ± standard deviation (SD) 10.53 ± 3.44 years) and their parents (45 mothers and 45 fathers) were included in the study. Both parents of each child were asked to separately fill in the validated Polish version of the FDLQI questionnaire. Results: Comparing the FDLQI scores, the QoL of mothers was significantly more impaired than the QoL of fathers (13.44 ± 6.46 versus 9.53 ± 6.12 points; P  < 0.0001). In mothers, childhood psoriasis had a significantly greater impact in the areas of emotional distress ( P  = 0.007), dealing with other people's reactions ( P  < 0.0001), social life ( P  = 0.02), amount of time spent caring for the child's skin ( P  = 0.0001) and extra housework ( P  = 0.0005), compared to fathers. The FDLQI scores of both mothers and fathers were independent of the impairment of children's QoL or the severity of psoriasis, except for positive correlation between mothers' FDLQI scores and children's BSA ( R  = 0.31; P  = 0.03). Conclusions: Differences in the impact of childhood skin diseases on mothers' and fathers' well‐being should be taken into consideration while developing educational programmes for patients and their families. There is a need for further, multi‐centre research that would take into account geographical and cultural differences, in order to reliably assess the impact of childhood psoriasis on various aspects of caregivers' QoL.